Nail Fold Capillaroscopic Findings in Elderly Patient with Acrocyanosis - Maria Bibiana Leroux (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2016)
The Raynaud´s phenomenon (RP) is well known as the first sign of systemic scleroderma (SS) and related disorders. Its early diagnosis leads to a better understanding of the disease and favorable prognosis. The acrocyanosis is an acrosyndrome differing physiologically and clinically, that can be due to vascular etiology, systemic diseases,drugs, infections or other causes. We hereby present an elderly male patient, aged 62 years, with acrocyanosis with altered capillaroscopy, compatible with an early systemic scleroderma starting three months ago in the fingers. The patient is a heavy smoker of 40 daily cigarettes during several years, with a body mass index (BMI) of 20.7 with neither Raynard's phenomenon nor acrosclerosis or rheumatoid disease. There is no evidence of traumatism, cancer or systemic infection.Two months ago he presented an acute bacterial paronychia in the third finger of the right hand which is presently healing very well (Figures 1,2). Acrocyanosis due to low BMI, thromboangiitis obliterans and secondary RP were considered among the differential diagnosis.